A Quality Improvement Curriculum for Psychiatry Residents - Claudia L. Reardon; Roderick Hafer; Frederick J. P. Langheim; Elliot R. Lee; Jennifer M. McDonald; Michael J. Peterson; John Stevenson; Art Walaszek (MedEdPORTAL, 2020)
Introduction Quality improvement (QI) is an increasingly important aspect of health care and residency education. There is relatively little research describing QI curricula for residents in psychiatry. Although QI curricula have been published in MedEdPORTAL, the current resource represents the first such curriculum specific to psychiatry residents. This resource aims to present a QI curriculum for psychiatry residents. Methods The University of Wisconsin psychiatry residency program implemented a QI curriculum for our PGY 3 psychiatry residents in 2010. The initial version of the curriculum has undergone marked changes over the ensuing years, reflecting feedback received from learners and faculty instructors, as well as ongoing review of the literature, to ascertain best practices in this area of medical education. Steps taken have included faculty training, development of evaluation forms, and implementation of elements to increase accountability for successful, sustainable project development. Results During the 8 completed years of this curriculum, 77 PGY 3 psychiatry residents have completed it. The Quality Improvement Knowledge Application Tool adapted for psychiatry was completed by PGY 3 residents in advance of and upon completion of the curriculum for the first 2 years of the curriculum; results demonstrated a significant improvement in scores as a measurement of QI knowledge and skills. Thirty-one of 32 resident teams (97%) have implemented a QI project. Discussion Our QI curriculum for PGY 3 psychiatry residents has been successful in equipping residents with QI knowledge and having them implement QI projects.